Main criteria of sustainable natural fibre for efficient unidirectional biocomposites. (September 2019) - Bourmaud, Alain; Mérotte, Justin; Siniscalco, David; Le Gall, Maelenn; Gager, Victor; Le Duigou, Antoine; Pierre, Floran; Behlouli, Karim; Arnould, Olivier; Beaugrand, Johnny; Baley, Christophe
Abstract: This paper investigates biochemical, morphological and mechanical properties of a large range of plant fibres explored with the same methods. Biochemical results clearly exhibit strong differences between gelatinous, i.e. flax and hemp, and xylan type, i.e. jute and kenaf, cell walls. These differences into parietal composition have an impact on cell wall stiffness, highlighted through nanoindentation and atomic force microscopy measurements, but also on fibre individualisation, due to variations into fibre bundles cohesion. In addition, the morphology and particularly the lumen size induces apparent density differences. Moreover, the influence of fibre morphology and properties is demonstrated on UD materials. Finally, longitudinal Young's modulus of each plant fibre batches is back-calculated from UD stiffness by an inverse method; the results obtained are in accordance with the values in the literature values, proving the interest of this method to estimate longitudinal Young's modulus of short plant fibres.